THE EFFECT OF REFLECTIVE TEACHING AND THE USE OF TEXT MODELS ON STUDENT ENGAGEMENT AND ACHIEVEMENT IN ENGLISH CLASSES - Febriyanti, Laili (SIMPLE: International Journal of English Education, 2025)
This study investigates the impact of Reflective Teaching combined with the use of text models on student engagement and achievement in English writing classes at MTs Nurul Huda Kragan. The research employs a mixed-method approach, integrating quantitative data from pre-test and post-test scores with qualitative insights derived from observations and semi-structured interviews. Results demonstrate a significant increase in student participation, from an average of 50% to 76.42%, and an improvement in achievement scores, with a rise from 58.44 to 85.57 after the intervention. The Reflective Teaching approach enabled teachers to adapt their methods through continuous self-assessment, fostering a more interactive and supportive classroom environment. Additionally, the use of text models facilitated students’ understanding of writing structure and content, enhancing their critical thinking and creativity. This study concludes that the combination of Reflective Teaching and text models is an effective strategy to address challenges in writing instruction, offering valuable insights for educators seeking to improve learning outcomes in similar contexts.